2020
DOI: 10.1186/s12903-020-01222-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different doses of radiation on morphogical, mechanical and chemical properties of primary and permanent teeth—an in vitro study

Abstract: Background: Radiotherapy, applied to the head and neck region, can cause radiation side effects such as reduction of saliva and radiation caries. The aim of this study was to perform an in vitro assessment of the effects of radiation therapy on the morphological, mechanical, and chemical properties of primary and permanent teeth. Methods: One hundred four extracted human teeth (52 impacted wisdom teeth, 52 primary molar teeth) were used. The teeth were divided into two parts in the mesiodistal direction. Of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
3
29
0
1
Order By: Relevance
“…This was demonstrated in the present study by the ESEM, as the irradiated sample showed a merging of both prismatic and interprismatic structures, with distorted prismatic peripheries. This is in agreement with findings by Duruk et al [14], Bakr [21] and Rodrigues et al [31]. Furthermore, this change in the enamel crystalline structure was suggested as one of the factors related to the increased risk of dental caries following radiation therapy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This was demonstrated in the present study by the ESEM, as the irradiated sample showed a merging of both prismatic and interprismatic structures, with distorted prismatic peripheries. This is in agreement with findings by Duruk et al [14], Bakr [21] and Rodrigues et al [31]. Furthermore, this change in the enamel crystalline structure was suggested as one of the factors related to the increased risk of dental caries following radiation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…The VHN results showed that microhardness of gamma-irradiated enamel decreased insignificantly, which agrees with the findings by Duruk et al [14], and Klarić Sever et al [29], yet differs from results in other studies [8], [25] that recorded an increase in surface microhardness with cumulative doses higher than 30 Gy. The crystal structure of the mineralized tissues may be subjected to some structural changes due to the ionizing radiation, which can modify their physical properties, including the microhardness.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This could perhaps be the result of the more inorganic structure of enamel, which is more resistant to both bleaching and irradiation in comparison with dentin. Gülsüm et al (39) reported that microhardness of all layers of the enamel of permanent teeth decreased (from surface to deeper layers) with an increase in irradiation dose from 20 to 60 Gy, while other studies indicate a decrease in surface microhardness of dentin (43)(44)(45), which is further explained by high water content in dentin (10%), obliteration of dentinal tubules, degeneration of collagen fibers, and greater effect of free radicals released after radiation (46). One detailed study confirmed that after cumulative radiation of 30 and 60 Gy, no morphological alteration in the prismatic enamel structure was observed, but the interprismatic portion became more evident with the increase in the radiation dose.…”
Section: Discussionmentioning
confidence: 99%